El currículum vivido del licenciado en enfermería: construyendo y (des) construyendo al profesional del cuidado enfermero que vive en mí. - Zarza Arizmendi, María Dolores (2016)
The thesis “The Lived Nursing Bachelor Curriculum: Constructing and Deconstructing the Nursing Care Professional Who Lives in Me” belongs to line of research in nursing education of both, the National University of Trujillo, Peru, and the National School of Nursing and Obstetrics of the National Autonomous University of Mexico. The purpose of this research is to deepen into the reflection on the day-to-day lived curriculum and the formal planned curriculum lived within defined times and spaces. Twenty two students organized in three focus groups and who were in-depth interviewed participated in the study. All these students were enrolled in the 8th semester of their bachelor program. The sampling saturation was reached through the snow-ball methodology. The results contributed to further reflect on the representations, beliefs, preferences, ideologies, etcetera, which all together constitute the student’s cultural foundation. The lived reality of the nursing student is the product of academic, social, and working-related networks, as well as the context with its diverse-particular situations, which all influence on the formation. In this day-to-day living, the students find values which they internalize along their formation process within the classrooms, the laboratories, the hospitals. During the study, two main categories emerged: 01: student and academician day-to-day lived curriculum, with three subcategories: 01-1: student and academician day-to-day within the classroom – times and tasks in the theory, 01-2: student and academician day-to-day within the hospital – times and tasks in the clinical practice, and 01-3: student and academician day-to-day in the community, and 02: transcending the concepts; with two sub-categories: 02-1: from the student information into becoming a professional, and 02-2: building professional identity. Final considerations: The theoretical scope of “The Lived Nursing Bachelor Curriculum: Constructing and Deconstructing the Nursing Care Professional Who Lives in Me” here described, Requested suggested translation for the sole and exclusive use by The National Autonomous University of Mexico represents a fundamental area of study to further understand the phenomena lived by nursing students along their formation, and therefore to fit and harmonize the study plans accordingly. From the conclusions and premises generated by this study, the importance of strengthening the identity of the student as a nurse since the beginning of their careers is highlighted, a situation which leads us to design and implement strategies which can consolidate solid student-academician links in order to promote the student’s identity with the profession and its fundamental values.